Знакомая незнакомка: Рец. на кн.: «Заре Григорьевне Минц посвящается…: Публикации, воспоминания, статьи. К 90-летию со дня рождения» [A Known Unknown: “Zare Grigor’evne Mints posviashchaetsia. Publikatsii, vospominaniia, stat’i. K 90-letiiu so dnia rozhdeniia.” A review article] - Sergei Dotsenko (Slavica Revalensia)
This is a review of the collection of articles dedicated to the memory of Prof. Zara Mints (1927—1990) published on occasion of her 90th birthday by Tallinn University Press.